Analisis model pembelajaran online dan offline yang diterapkan guru pada masa pandemi covid-19 di sekolah dasar - Idola Septria Irma; Claudia Lorenza (Universitas Negeri Padang, 2022)
He selection of the right learning model will be more effective than choosing the best learning model, because basically there is no best and most superior learning model. This study aims to analyze online learning and offline learning that can run well, so that educational goals can be achieved precisely during the COVID-19 pandemic. This research was conducted at SD Negeri 33 Koto Taratak. The type of research used is a literature study, with the research method used is qualitative research. The research was conducted by analyzing online and offline learning models based on the elements of the learning model consisting of syntax, social systems, reaction principles, support systems, and instructional and support impacts. The application of the online learning model at SD Negeri 33 Koto Taratak is carried out with the help of the WhatsApp application, and the offline learning model at SD Negeri 33 Koto Taratak uses the method of collecting assignments to school. The results of this research analysis can be used as a reference by teachers in implementing online and offline learning models during the Covid 19 pandemic